Balancing Opposing Forces—A Nested Process Evaluation Study Protocol for a Stepped Wedge Designed Cluster Randomized Controlled Trial of an Experience Based Codesign Intervention: The CORE Study. Issue 1 (17th October 2016) - Palmer, Victoria Jane; Piper, Donella; Richard, Lauralie; Furler, John; Herrman, Helen; Cameron, Jacqui; Godbee, Kali; Pierce, David; Callander, Rosemary; Weavell, Wayne; Gunn, Jane; Iedema, Rick
Background: Process evaluations are essential to understand the contextual, relational, and organizational and system factors of complex interventions. The guidance for developing process evaluations for randomized controlled trials (RCTs) has until recently however, been fairly limited. Method/Design: A nested process evaluation (NPE) was designed and embedded across all stages of a stepped wedge cluster RCT called the CORE study. The aim of the CORE study is to test the effectiveness of an experience-based codesign methodology for improving psychosocial recovery outcomes for people living with severe mental illness (service users). Process evaluation data collection combines qualitative and quantitative methods with four aims: (1) to describe organizational characteristics, service models, policy contexts, and government reforms and examine the interaction of these with the intervention; (2) to understand how the codesign intervention works, the cluster variability in implementation, and if the intervention is or is not sustained in different settings; (3) to assist in the interpretation of the primary and secondary outcomes and determine if the causal assumptions underpinning the codesign interventions are accurate; and (4) to determine the impact of a purposefully designed engagement model on the broader study retention and knowledge transfer in the trial. Discussion: Process evaluations require prespecified study protocols but finding a balance between their iterative nature and the structure offered by protocol development is an important step forward. Taking this step will advance the role of qualitative research within trials research and enable more focused data collection to occur at strategic points within studies.